Determinan Ketepatan Waktu Pelaporan Keuangan Perusahaan Subsektor Transportasi Terdaftar di BEI - Rahayu Pangestuti; Anita Wijayanti; Yuli Chomsatu Samrotun (Politeknik Ganesha Medan, 2020)
Timeliness is a must in a corporate financial reporting and one of the requirements for information to be useful and relevant to the existing situation. This research’s purpose to test and analyze the impact of profitability, liquidity, leverage, firm size, and audit opinion on timeliness of financial reporting. Transportation sub sector companies listed on Indonesia Stock Exchange in 2016-2018 are the population of this study, as much 42 companies. The total’s samples is 40 transportation companies, selected using purposive sampling method. Data analysis technique using logistic regression test. The result showed the timeliness of financial reporting influenced by leverage and audit opinion, but not influenced by profitability, liquidity, and firm size.